Прибор для дистанционного управления нагрузками посредством ИК пульта - Хроменко, А. Г.; Глухов, О. В. (ХНУРЕ, 2019)
In this article, we have developed and improved a remote control circuit for loads based on a logical pulse counter CD 4017. Various options for its use are described, as one of them - as a device for controlling the illumination of rooms, using relay switches.
Keywords: Прибор для дистанционного управления; ИК пульт